Study of Mechanical and Morphological Properties of Polypropylene Blended with EPDM Rubber Powder from Automotive Door Seals - Thongsang, Sirinthorn; Kengkla, Nattarat; Boonjan, Nuntinee; Tiraditsakul, Kamonthip (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This research studied the mechanical and morphological properties of polypropylene blended with Ethylene Propylene Dine Monomer (EPDM) rubber powder from automotive door seals. EPDM rubber powder was prepared as non-devulcanized and devulcanized by a thermo-mechanical method. The devulcanization of EPDM rubber powder in the crushing stage on a two-roll mill was studied at 220 °C and 230 °C, and a roller speed of 40 rpm for 25 minutes, and then further mashed in an internal mixer at 200 °C, and a rotor speed of 140 rpm for 10 minutes. Then, the devulcanization ability of the rubber was determined using the Soxhlet Extraction method to select the appropriate temperature. Both types of EPDM powder were mixed in polypropylene (PP) in the ratio of 0/100, 10/90, 20/80, 30/70, and 40/60 %wt. using an internal mixer and molded into a sheet by a hot press. It was found that the rubber devulcanization in the crushing stage on a two-roll mill with a temperature of 230 °C had a higher sol content than that of 220 °C, indicating a better ability to devulcanize. The tensile modulus of PP blends decreased with increasing both types of EPDM rubber powder, while the elongation at break and impact strength increased. The tensile strength tended to decrease when increasing with non-devulcanized and devulcanized EPDM at 30 and 40 %wt., respectively. The addition of devulcanized EPDM into PP gave rather better mechanical properties than that of non-devulcanized EPDM. The reason was that the devulcanized EPDM was a smaller powder and had a good dispersion, resulting in more surface area for adhesion with the PP matrix. In addition, the devulcanized EPDM that was scissored crosslinks became the free molecular chains, leading to a greater compatibility with PP.